CHALLENGES FOR RIAU PROVINCE TOWARDS ASYMMETRIC DECENTRALIZATION - Herman; Indah Susilowati; Retno Sunu Astuti; Hardi Warsono (RADJA PUBLIKA, 2023)
Riau Province is one of the areas rich in oil and other agricultural products. Therefore, Riau deserves to demand asymmetric decentralization as other places that have granted this decentralization right. The purpose of this paper is to explore the potential or things that are considered appropriate to be used as reasons why Riau Province has the right to be made special autonomy or asymmetric decentralization because specific areas that are rich in natural resources. This study uses a qualitative approach using a theory-based system where theory functions as a framework for understanding problems critically. The data collection tool used is the document method that the author collects. From the results of the study, it can be concluded that if viewed from the theory of UGM PLOD Research, Riau deserves asymmetric decentralization when viewed from historical and conflict factors, social and cultural factors, potential and economic growth factors, accelerated development factors, and government capacity. This was due to the joining of Siak Indrapura's work through Sultan Syarif Kasim II to the State of Indonesia and the abundant wealth of Riau. Meanwhile, the factors that do not support the above theory are geographical factors due to the separation of the Riau Islands from Riau itself. To support asymmetrical decentralization, quality resources from the people of Riau are needed so that the mentality of corruption can be removed. In addition, of course, the ability of the Riau people's representatives at the center to lobby the government so that asymmetric decentralization can be realized.